1970
DOI: 10.3329/bjvm.v6i2.2337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic and vitamin B-complex in lead acetate induced toxicities in mice

Abstract: The experiment was performed on 25 adult mice, (Swiss albino), weighing about 25 gm, maintained on standard pellet diet and drinking water ad libitum. All the mice were randomly divided into five equal groups (5x5). Each group comprised of five mice was marked as group A, B, C, D and E. In the present study an attempt has been taken to study the effect of Garlic and vitamin B-complex in lead induced toxicities in mice with the observation of some parameters as toxic signs and body weight, some haematological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 5 publications
10
23
0
Order By: Relevance
“…The change in the body weight of the sucklings exposed to Pb only was lower than that of the other groups. Our findings on the effect of lead on the body weight are in line with previous studies in which reduced weight gains after intoxication with lead acetate in adult mice (Khan et al 2008) and rats (Szymezak, Zechalko and Biernat 1983) have been reported. This supports the hypothesis that Pb does influence growth during childhood.…”
Section: Discussionsupporting
confidence: 95%
“…The change in the body weight of the sucklings exposed to Pb only was lower than that of the other groups. Our findings on the effect of lead on the body weight are in line with previous studies in which reduced weight gains after intoxication with lead acetate in adult mice (Khan et al 2008) and rats (Szymezak, Zechalko and Biernat 1983) have been reported. This supports the hypothesis that Pb does influence growth during childhood.…”
Section: Discussionsupporting
confidence: 95%
“…In the current study, prescription of combined vitamin E and lead resulted a significant increase in parameters including seminiferous tubules diameter, number of Sertoli cells and motility and viability of sperms. Positive effects of vitamins E, C, folic acid, thiamin, niacin and B 12 have been reported in genital system and sperm fertility parameters in males exposed to lead [5][6][7]47,48]. Another determinant of cell damage by lead is ALP enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed the ameliorative role of combined Allium sativum and vitamin B-complex against lead acetate-induced toxicity and have proved the potency of these combined substances [27]. It has been found that allicin role is not only ameliorative against lead toxicity, but the plant also contains chelating compounds capable of enhancing the elimination of lead [36].…”
Section: Discussionmentioning
confidence: 99%